FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT KOLEKTIBILITAS PEMBIAYAAN SEKTOR UMKM (STUDI KASUS : BANK SYARIAH XYZ KANTOR CABANG JAKARTA BARAT) - Raden Yogi Arieffiandi; Muhamad Firdaus; Hendro Sasongko (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The objectives of this study are to analyze the factors that affect the financing collectability in XYZ Sharia Bank branch office in West Jakarta, to formulate and recommend a strategic planning of the bank to reduce the level of Non-Performing Loans (NPF) in the future. Logistic regression and SWOT matrix were utilized as the methods of this study. Thus, the results showed that the factors influencing the financing collectability of XYZ Sharia Bank customers are financing agreement types, margin/profit sharing equivalent rate, economic sectors, and value of the company Altman Z-Score. From the analyses of both external and internal factors, it reveals that strategic factors are identified to reduce the value of NPF in XYZ Sharia Bank West Jakarta i.e. by performing defensive actions. The assessment results of the strategy in XYZ Islamic Bank, West Jakarta, in terms of SWOT in tightening the cost analysis of SME sector, are as follow: carrying out the process of cost analysis more carefully and thoroughly, and conducting HR personnel training, or sharing with other branches in the neighboring areas, anticipating over assessment by adopting an independent assessor, performing more detailed screening in doing financing disbursement, and maximizing the existing internal regulations related to the financing facility.Keywords: Collectable financing, logistic regression, SWOT, Altman Z-Score, SMEABSTRAKTujuan dari penelitian ini adalah menganalisis faktor-faktor yang berpengaruh terhadap kolektibilitas pembiayaan pada Bank Syariah XYZ kantor cabang Jakarta Barat dan merumuskan dan merekomendasikan perencanaan strategis Bank Syariah XYZ dalam rangka menekan tingkat Non Performing Loans (NPF) di masa yang akan datang. Metode penelitian ini menggunakan regresi logistik dan matriks SWOT. Hasil dari penelitian ini diperoleh faktor-faktor yang memengaruhi kolektibilitas pembiayaan oleh nasabah Bank Syariah XYZ adalah Jenis akad pembiayaan, tingkat equivalent rate margin/bagi hasil, sektor ekonomi, dan nilai Altman Z-Score perusahaan. Hasil analisis lingkungan eksternal dan lingkungan internal diperoleh faktor-faktor strategis yang dapat dimanfaatkan dalam menekan nilai NPF pada Bank Syariah XYZ Jakarta Barat dengan melakukan tindakan defensif. Hasil evaluasi strategi Bank Syariah XYZ Kantor Cabang Jakarta Barat dari segi SWOT dalam memperketat analisis pembiayaan sektor UMKM antara lain: melakukan proses analisis pembiayaan dengan lebih hati-hati dan menyeluruh, melakukan pelatihan tenaga SDM atau dengan melakukan sharing dengan cabang lain dalam wilayah yang berdekatan, mengantisipasi over penilaian dengan menggunakan penilai independen, melakukan screening lebih detail pada saat melakukan pencairan pembiayaan, dan memaksimalkan peraturan internal yang ada terkait pemberian fasilitas pembiayaan.Kata kunci: kolektibilitas pembiayaan, regresi logistik, SWOT, Altman Z-Score, UMKM